2020
DOI: 10.3168/jds.2019-18050
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Student Literature Review: Potential mechanisms of interaction between bacteria and the reproductive tract of dairy cattle

Abstract: Although the presence of bacteria has been characterized throughout the reproductive tracts of multiple species, how these bacteria may interact with the host has yet to be described. Previous reviews have described how pathogenic bacteria interact with the reproductive tract to cause infections such as metritis. This review aimed to summarize the knowledge related to pathogenic and nonpathogenic bacteria in various locations of the bovine reproductive tract and the possible mechanisms underlying host-microbe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Studies have come to similar conclusions with zebrafish, and researchers have found that L. rhamnosus acts both on the endocrine system and at the local level by inducing oocyte maturation 34,35 . This effect was also found in cows, where Lactobacillus secretes flavonoids to increase oocyte competency 36 . In conclusion, Lactobacillus in follicular fluid might promote egg maturation through its secretion or inhibit the growth of other pathogens to maintain a healthy developmental environment for the egg.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Studies have come to similar conclusions with zebrafish, and researchers have found that L. rhamnosus acts both on the endocrine system and at the local level by inducing oocyte maturation 34,35 . This effect was also found in cows, where Lactobacillus secretes flavonoids to increase oocyte competency 36 . In conclusion, Lactobacillus in follicular fluid might promote egg maturation through its secretion or inhibit the growth of other pathogens to maintain a healthy developmental environment for the egg.…”
Section: Discussionmentioning
confidence: 57%
“…Lactobacillus secretes flavonoids to increase oocyte competency. 36 In conclusion, Lactobacillus in follicular fluid might promote egg matura-tion through its secretion or inhibit the growth of other pathogens to maintain a healthy developmental environment for the egg.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, sections of the reproductive tract, like the vagina, cervix, uterus, and oviduct, support the growth of specific subsets of bacteria, but the microbial composition and diversity of each section could be influenced by those adjacent to it [ 45 , 46 ]. We observed a moderate correlation between the placental and vaginal microbiomes, but we also observed lower phylogenetic diversity in placental samples compared to vaginal samples and separate clustering of placental and vaginal samples in the principal coordinate scatter plot.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota also consists of pathogenic organisms capable of causing disease. In the postpartum dairy cow, for example, uterine infection (metritis) can have profound negative effects on reproductive efficiency, animal health, and reduce productivity after calving (Galvão et al, 2019 ; Owens et al, 2020 ; Moraes et al, 2021 ). A sterile uterus was previously thought to be a prerequisite for a healthy uterus and the establishment of pregnancy (Banchi et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%